Effect of Galangal Essential Oil Emulsion on Quality Attributes of Cloudy Pineapple Juice - Zhou, Wei; Sun, Yuefang; Zou, Liqiang; Zhou, Lei; Liu, Wei (Frontiers in Nutrition, 2021)
Galangal essential oil was obtained from the rhizomes of galangal with proven anti-inflammatory, antioxidant, antiviral, and antimicrobial properties, which was valuable in food industry. To explore the effect of galangal essential oil emulsion on the quality of fruit juice, the effects of 0.05%, 0.1%, 0.2% and 0.4% emulsion on the quality attributes were investigated, and their influence on physical stability, physicochemical properties, microbial quantity and aroma profiles of cloudy pineapple juice were also evaluated. The essential oil emulsion of galangal is a milky white liquid with strong aroma of Alpinia. The value of pH (from 4.35 to 5.05) increased with the increase of emulsion concentration, and there was no significant difference in particle size between 199.30 nm and 218.63 nm. The results showed that galangal essential oil emulsion was stable and the stability of cloudy pineapple juice was significantly enhanced with the essential oil emulsion determined using LUMiSizer. The cloudy pineapple juice with 0.2% essential oil emulsion had the most stability after 4 days of storage. The lightness of the cloudy pineapple juice increased instantly with essential oil emulsion addition. In addition, the microbial quantity of cloudy pineapple juice was depressed by separate essential oil emulsion or combining essential oil emulsion with thermal treatment to hold a longer shelf life. Microbial counts in treated by essential oil emulsion combined with thermal treatment cloudy pineapple juice increased from 1.06 log CFU/mL to 1.59 log CFU/mL after 4 days storage at 25 °C. Besides, the pH and total soluble solids (TSS)showed an increasing trend slightly, however, the value of titratable acidity (TA), free radical scavenging capacity (DPPH) and ascorbic acid content (Vc) of cloudy pineapple juice showed no significant change. Finally, the results electronic nose showed that the aroma components of pineapple juice were changed by essential oil emulsion and heat treatment, and the difference was especially evident in the content of sulfur compounds, sulphur organic compounds and aromatics compounds. Consequently, the results indicated that the 0.2% galangal essential oil emulsion can be used as juice additives to improve the quality attributes and extend the shelf-life of cloudy pineapple juice.